Successfully addressing non-compliance with behavioral and social infection control measures is a critical component in management of healthcare worker COVID-19 outbreaks: learning outcomes from the first staff outbreak in the main maternity hospital in Qatar - Petkar, Hawabibee Mahir; George, Bonnie; Mostafa, Eman; Caseres-Chiuco, Imelda; Mohamed, Mahmoud; Jeremijenko, Andrew; Coyle, Peter Valentine; AlKhatib, Hebah Atef Mohammad; Benslimane, Fatiha; Bensaad, Meryem; Al-Barghouthi, Bayan; Petkar, Zaid Mahir; et al. (Frontiers in Public Health, 2025)
BackgroundNosocomial healthcare worker (HCW) SARS-CoV-2 outbreaks are well recognized. Contact tracing, use of surgical masks, hand hygiene and social distancing can prevent spread. Social and behavioral factors play an important role in outbreak control. We provide an integrated report on management of our first outbreak and lessons learned.MethodsDemographic and test result information was extracted from the outbreak report. Infection control practices were audited using a standardized behavior assessment tool. Exposure risk was ascertained using World Health Organization definitions. Cases were identified by reverse transcriptase polymerase chain reaction (RT-PCR) or by seroconversion. Whole genome sequencing was performed on RT-PCR positive cases. Statistical analyses were performed in RStudio. Incidence rates and relative risk were used as measures of effect.ResultsAlmost 10% of HCWs developed infection; high risk exposures had a statistically higher risk. All isolates were clade 20C. Consistent with the hypothesis, the epidemiological curve showed a mixed outbreak, initially common source, with subsequent sporadic cases possibly from environmental contamination. Interventions: focused on contact tracing and strict compliance with social distancing, PPE use, hand hygiene and environmental cleaning, supported by rigorous audits. Lessons learned: root cause was a symptomatic HCW reporting to work in breach of policy. Contributing factors: failure to challenge the breach, lax managerial oversight, lounge overcrowding and insufficient cleaning staff.DiscussionManagement required a multi-pronged approach. Full delineation of the outbreak required contact tracing, and correlation of epidemiological information with Ct values, whole genome sequencing and serology. Strategies to address social and behavioral factors should be devised considering the local institutional culture Good leadership, ‘speaking up’ for patient safety and linking individual IPC practices to annual evaluations are effective measures.